Population dynamics and feeding ecology of the western tubenose goby (Proterorhinus semilunaris) in the Stugna River, Dnieper River basin, Ukraine - Didenko Alexander; Volikov Yuriy; Gurbyk Alexander; Kruzhylina Svitlana; Buzevych Igor; Bekh Vitaliy (Oceanological and Hydrobiological Studies)
The study investigated the inter-annual and seasonal population dynamics, as well as the feeding habits of the western tubenose goby Proterorhinus semilunaris in an invaded river close to its natural range (Dnieper River basin). Material was collected monthly in 2015–2016 and 2018 at one sampling site located in the Stugna River, at a distance of 1100 m from the point where it enters the Kaniv reservoir. Catch-per-unit-efforts (CPUE) of this species at the sampling site varied considerably, both between different months within a given year and between the analyzed years, from 1.1 to 127.1 fish 100 m-2. Peak abundances were observed in July in both 2015 and 2018, and then dropped sharply in the following months. The western tubenose goby is characterized by a protracted spawning season, lasting from April to July. A total of 50 prey taxa were recorded in the diet of the western tubenose goby at the sampling site, among which chironomids were the most abundant and most frequently encountered, followed by cladocerans. This gobiid at the sampling site preyed mainly among submerged vegetation, where phytophilous chironomids were the most important prey.